Characterization data on the topical carrier DDC642 - Eline Desmet; Stefanie Bracke; Katrien Forier; Lien Taevernier; Marc C.A. Stuart; Bart De Spiegeleer; Koen Raemdonck; Mireille Van Gele; Jo Lambert (Data in Brief, 2016)
This article contains original data, figures and methods used in the characterization of the liposomal carrier ‘DDC642’ for topical applications, described in “An elastic liposomal formulation for RNAi-based topical treatment of skin disorders: proof-of-concept in the treatment of psoriasis” (Desmet et al., 2016) [1]. Several elastic liposomal formulations have been evaluated for their ability to encapsulate and deliver RNA interference (RNAi) molecules to cultured primary skin cells. The efficiency and effectiveness of these liposomes were compared to that of our previously characterized liposomes, the ‘SECosomes’ (SEC) (Geusens et al., 2010) [2]. After selection of a potential superior carrier, based on encapsulation and transfection efficiency data (Desmet et al., 2016) [1], the selected DDC642 liposomes were characterized more in-depth. Herein, a detailed characterization of the DDC642 liposome and RNAi-loaded lipoplexes is given, including the matching protocols. Keywords: Gene therapy, Lipid-based nanoparticle, Liposome, RNA interference, Topical drug delivery